2004
DOI: 10.3201/eid1009.040101
|View full text |Cite
|
Sign up to set email alerts
|

SARS Antibody Test for Serosurveillance

Abstract: A standardized and rapid peptide-based SARS assay is characterized for sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…For SARS-CoV infection, it has been shown that nucleotides 952-1530 of the spike protein gene of SARS-CoV encoded a 193-amino acid fragment responsible for attaching to the receptor for SARS-CoV, angiotensin-converting enzyme 2 [9]. Furthermore, we, and also others, have shown that patients with SARS produced antibody response against the spike protein of SARS-CoV [3,10,11], and it has been demonstrated that the spike protein is the major target for passive immunization [12,13]. In studies that determine the relative importance of humoral and cell mediated immunity for protection against SARS-CoV infection, it was confirmed that neutralizing antibody, when administered by passive immunization, was crucial in conferring protection [14], whereas T-cell immunity was unable to lead to protection [15].…”
Section: Introductionmentioning
confidence: 51%
“…For SARS-CoV infection, it has been shown that nucleotides 952-1530 of the spike protein gene of SARS-CoV encoded a 193-amino acid fragment responsible for attaching to the receptor for SARS-CoV, angiotensin-converting enzyme 2 [9]. Furthermore, we, and also others, have shown that patients with SARS produced antibody response against the spike protein of SARS-CoV [3,10,11], and it has been demonstrated that the spike protein is the major target for passive immunization [12,13]. In studies that determine the relative importance of humoral and cell mediated immunity for protection against SARS-CoV infection, it was confirmed that neutralizing antibody, when administered by passive immunization, was crucial in conferring protection [14], whereas T-cell immunity was unable to lead to protection [15].…”
Section: Introductionmentioning
confidence: 51%
“…Furthermore, the creation of scFvs fused to other protein is believed to lead to the formation of dimers [16], which should have greater avidity and stability than original monovalent scFvs, and can be used, for example, for detection purposes. At present, the laboratory tests that can be applied for routine diagnosis of SARS mainly include detecting viral genome by PCR involving in RT-PCR [19][20][21][22] and RT-LAMP [23], and detecting serum antibodies using SARS-CoV from Vero cell culture by ELI-SA [24][25][26], IFA [27][28][29], and NT [2]. However, there is little progress in detection of SARS-CoV using scFv-antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This assay provided a high degree of sensitivity (95.9%) for convalescent serum samples and specificity close to 90% [16]. Moreover, a peptide-ELISA has been used for retrospective serosurveillance of SARS [80][81]. This assay has been developed by epitope mapping, using synthetic peptides from the spike, the membrane and nucleocapsid protein sequences of SARS-CoV.…”
Section: A3 Hepatitis a Virus (Hav) Infectionmentioning
confidence: 98%